Instructional Supervision Models Affecting the Change of Teaching Behaviors of Science Teachers - Pimwapee , Komsan; Sudrung, Jurairat (Journal of Education Studies, Chulalongkorn University, 2020)
The research was aim to (1) study instructional supervision models affecting the change of teaching behavior of science teachers. (2) compare instructional supervision models affecting the change of teaching behavior of science teachers. The samples used in this study were science teacher at elementary level. The sample was 357 teachers who were randomly assigned to the systematic random sampling. The research instruments were the questionnaire on the instructional supervision models affecting the change of teaching behavior of science teachers. Then the basic information of the sample and the instructional supervision models were applied. change of teaching behavior of science teachers. Frequency, percentage, mean, standard deviation and multiple regression analysis (MRA). The results of the study on the instructional supervision models affecting the change of teaching behavior of science teachers found that: (1) clinical supervision self-directed development and administrative monitoring were the variables affecting the change in teaching behavior of the science teachers. At the .05 level (2). compare instructional supervision models affecting the change of teaching behavior of science teachers. When the science teacher was supervised the clinical supervision (ß = .45), followed by self-directed development (ß = .22) and administrative monitoring (ß = .15). and clinical supervision model affecting the change of teaching behavior of science teachers 1) the instructional planning (ß = .45), 2) the use of teaching media (ß = 41). 3) Instructional activities (ß = .38) 4) Measurement and evaluation (ß = .32)